2011
DOI: 10.1017/s1751731110001710
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal development of dairy calves fed low- or high-starch concentrate at two milk allowances

Abstract: The objective was to study the effect of type of concentrate with varying starch and fibre content on growth and gastrointestinal development in preweaned dairy calves. Thirty-two newborn Danish Holstein male calves were allocated to four treatment groups in eight blocks of four calves. An experimental low-starch, high-molasses, high-fibre (EXP) concentrate or a traditional high-starch (TRA) concentrate were fed either at a high (HIGH; 2 3 3.2 kg/day) or a low (LOW; 2 3 1.6 kg/day) whole milk allowance in a 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 35 publications
6
15
0
4
Order By: Relevance
“…The in vitro studies shown that using zinc as an organic chelate complex or as a preparation obtained via biosorption have a better influence on fermentation products in a hen's caecum than inorganic salts [20,21] . Our results confirm studies conducted by other authors who noted that micronutrients fed to hens as organic compounds have better digestibility than inorganic salts [37] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro studies shown that using zinc as an organic chelate complex or as a preparation obtained via biosorption have a better influence on fermentation products in a hen's caecum than inorganic salts [20,21] . Our results confirm studies conducted by other authors who noted that micronutrients fed to hens as organic compounds have better digestibility than inorganic salts [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the influence of potential feed additives obtained with the biosorption on the processes occurring in the hens' caecum, which is of great importance to the health and productivity of the animals, is still not known. The studies conducted in vitro shows that feed additives obtained this way do not have a negative influence on fermentation processes occurring in the caecum of laying hens and should not have a negative influence on the animals' health [19][20][21] . In this study, we present the results of in vivo research on the fermentation process in the caecum of laying hens fed with the addition of zinc (II) brought in via the biosorption method, and compared it with the zinc (II) chelate complex.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the case of horses, prolonged and untreated obesity increases the risk of development of metabolic diseases such as equine metabolic syndrome (EMS), strongly associated with insulin resistance (IR), laminitis and hyperinsulinemia. Considering these facts, the obesity in horses leads to life-threatening conditions [3,5,29,30] . The obesity in horses is often neglected by the owners, and sometimes it is difficult to determine by the veterinary clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is investigated on two main levels affecting the carbohydrate and lipid metabolism: genetic and environmental predisposition such as physical activity and nutrition/diet [1][2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Observations were performed under inverted and epifluorescent microscope at magnification 100 × and 50 ×, respectively. For SEM observations, cultures were prepared as described previously [17,19]. Briefly, the procedure included (i) fixation in 2.5% glutaraldehyde in DMEM; (ii) washing using HBSS; (iii) dehydrated in a graded ethanol series (50% -100%); (iv) air-drying for 30 min at room temperature and (v) coating with gold using 300-second program (Edwards, Scancoat six).…”
Section: Analysis Of Chondrogenic Nodules Formation and Extracellularmentioning
confidence: 99%